1996
DOI: 10.1021/jm9506736
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Modification of Acidity in Cholecystokinin B Receptor Antagonists:  N-(1,4-Benzodiazepin-3-yl)-N ‘-[3-(tetrazol-5-ylamino)phenyl]ureas

Abstract: The design, synthesis, and biological activity of a novel series of CCK-B receptor antagonists (1) which incorporate a tetrazol-5-ylamino functionality attached to the phenyl ring of the arylurea moiety of L-365,260 are described. In these compounds, the acidity of the tetrazole was gradually modified by utilization of simple conformational constraints, and X-ray crystallographic data were obtained to support the conformational depenence of the pK(a) of the aminotetrazoles. Compounds to emerge from the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Initial efforts aimed at creating chiral 1,4-and 1,5-benzodiazepine-based CCK 2 antagonists led to the development of compound (L-365,260) [23], a 1,4-benzodiazepine, whose biological testing has progressed to human studies that showed its capability of reversing the anxiogenic effects produced by tetragastrin [24], but its ineffectiveness in patients with panic disorder [25]. Other 1,4-benzodiazepine-based CCK 2 antagonists based on the paradigm of compound L-365,260 [23] were compound GR 199114X [26] which lacks a charged functionality, compounds L-736,380 [27] and Z-360 [28] which contain acidic substituents, and compounds L-740,093 [29] and YF476 [30], which contain basic substituents. Consequently, McDonald et al [31] have reported the synthesis of series of 1,3,4-benzotriazepine-based CCK 2 R antagonists which are achiral and maintained selectivity over CCK 1 R. Further, they reported optimization of 1,3,4-benzotriazepine-based CCK 2 R antagonists so as to obtain potent, orally active inhibitors of gastrin-mediated gastric acid secretion [32].…”
Section: Introductionmentioning
confidence: 99%
“…Initial efforts aimed at creating chiral 1,4-and 1,5-benzodiazepine-based CCK 2 antagonists led to the development of compound (L-365,260) [23], a 1,4-benzodiazepine, whose biological testing has progressed to human studies that showed its capability of reversing the anxiogenic effects produced by tetragastrin [24], but its ineffectiveness in patients with panic disorder [25]. Other 1,4-benzodiazepine-based CCK 2 antagonists based on the paradigm of compound L-365,260 [23] were compound GR 199114X [26] which lacks a charged functionality, compounds L-736,380 [27] and Z-360 [28] which contain acidic substituents, and compounds L-740,093 [29] and YF476 [30], which contain basic substituents. Consequently, McDonald et al [31] have reported the synthesis of series of 1,3,4-benzotriazepine-based CCK 2 R antagonists which are achiral and maintained selectivity over CCK 1 R. Further, they reported optimization of 1,3,4-benzotriazepine-based CCK 2 R antagonists so as to obtain potent, orally active inhibitors of gastrin-mediated gastric acid secretion [32].…”
Section: Introductionmentioning
confidence: 99%
“…The N-(3-aminophenyl)-N-methylcyanamide intermediates 17e19 were prepared from 3-nitro-aniline 8. Cyanamide 15 was obtained in 93% yield [32]. After methylation of the cyanamide moiety and reduction of the nitro moiety, 17 was obtained in 72% overall yield.…”
Section: Chemistrymentioning
confidence: 99%
“…Therefore, further modifications were performed on the tetrazole moiety of L-368,730 in order to influence bioavailability by modulating the pK A of the acidic moiety by means of structural manipulations around the tetrazole group. 157 From this study, the aminotetrazole group was chosen as acidic moiety, because its pK A (6.0) is substantially higher than that of the tetrazole itself. Compounds resulting from this strategy, such as L-736,380 (27) and its analogue L-738,425, in which a 2-tetrazolyl-isoindolyl moiety replaces the 3-(N-methyl-N-tetrazolyl)aminophenyl of 27, are among the most potent and, in the case of L-738,425 [CCK 2 IC 50 ¼ 0.11 nM, CCK 1 /CCK 2 ¼ 37,000], most selective CCK 2 antagonists so far reported.…”
Section: Cck 2 Receptor Antagonistsmentioning
confidence: 99%
“…However, these acidic compounds are significantly less brain penetrant than the prototype L-365,260 (22). 157 Only with the introduction of cationic water solubilizing groups, particularly within the C-5 substituent, the oral bioavailability was improved. Such strategy was initially prompted by the 4-fold increase in plasma concentration after oral dosing in rats, with respect to L-365,260, achieved in the case of the 2-pyridyl substituted derivative 28.…”
Section: Cck 2 Receptor Antagonistsmentioning
confidence: 99%